Field emission from mono and two-dimensional nanostructures. (2020) - Grillo, Alessandro; Giubileo, Filippo; Iemmo, Laura; Luongo, Giuseppe; Urban, Francesca; Passacantando, Maurizio; Di Bartolomeo, Antonio
Abstract: In recent years, nanostructured materials have been deeply investigated for field emission applications. The exploitation of different geometries and morphologies is a key ingredient for the realization of proficient field emitter devices. In this work, we highlight the features of two differently shaped nanostructured materials such as molybdenum disulphide and gallium oxide. We show that Mo S 2 nanoflowers and β -Ga2 O3 nanopillars can achieve different field emission performance in terms of maximum current density, turn-on field and field enhancement factor.